2006
DOI: 10.1172/jci28341
|View full text |Cite
|
Sign up to set email alerts
|

The neurofibromin GAP-related domain rescues endothelial but not neural crest development in Nf1-/- mice

Abstract: Neurofibromatosis type I (NF1; also known as von Recklinghausen's disease) is a common autosomaldominant condition primarily affecting neural crest-derived tissues. The disease gene, NF1, encodes neurofibromin, a protein of over 2,800 amino acids that contains a 216-amino acid domain with Ras-GTPaseactivating protein (Ras-GAP) activity. Potential therapies for NF1 currently in development and being tested in clinical trials are designed to modify NF1 Ras-GAP activity or target downstream effectors of Ras signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…However, the malignant phenotypes of neurofibromin-deficient MPNST cells cannot be totally rescued by the GAP domain reconstitution alone (38,39). Furthermore, RAStargeted therapeutic approaches, such as S-trans, trans-farnesylthiosalicylic acid, have provided limited efficacy in clinical studies of NF1 (8,40).…”
Section: Discussionmentioning
confidence: 99%
“…However, the malignant phenotypes of neurofibromin-deficient MPNST cells cannot be totally rescued by the GAP domain reconstitution alone (38,39). Furthermore, RAStargeted therapeutic approaches, such as S-trans, trans-farnesylthiosalicylic acid, have provided limited efficacy in clinical studies of NF1 (8,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although NF1 À/À mice are lethal at E13.5 because of cardiac defect, the CMVCre; HA-GRD; NF1 À/À mice survive to birth with normal cardiac anatomy. However, these mice succumb to death at perinatal period because of overgrowth of neural crest-derived tissues (Ismat et al, 2006). These findings could be interpreted to indicate that not all of the phenotypes seen in NF1 mutations are solely secondary to Ras dysregulation.…”
Section: Biology Of Neurofibrominmentioning
confidence: 94%
“…In addition, Ismat et al (2006) showed that mice expressing the NF1 GRD only partially rescue the phenotypes seen in NF1…”
Section: Biology Of Neurofibrominmentioning
confidence: 99%
“…Slides were deparaffinized, washed once in PBS, incubated in 0.1 mg/ml Lectin (SIGMA, L-4895) in PBS at room temperature in darkness for 2 h. Then the slides were washed 3 times with PBS, mounted with fluorescent mounting media (Vector Laboratories), and covered with a coverslip. The cell size was measured with image J software as indicated previously (60).…”
Section: Analysis Of Fibrosismentioning
confidence: 99%